2015
DOI: 10.3390/v7072809
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Underlying the Envelope Glycoproteins of Hepatitis C Virus: Structural and Functional Consequences and the Implications for Vaccine Design

Abstract: In the 26 years since the discovery of Hepatitis C virus (HCV) a major global research effort has illuminated many aspects of the viral life cycle, facilitating the development of targeted antivirals. Recently, effective direct-acting antiviral (DAA) regimens with >90% cure rates have become available for treatment of chronic HCV infection in developed nations, representing a significant advance towards global eradication. However, the high cost of these treatments results in highly restricted access in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 315 publications
(492 reference statements)
0
37
0
Order By: Relevance
“…Notably, within infected individuals, the virus actively evades the immune system [19] and evolves into a large number of quasispecies through error-prone replication [20]. This presents a major challenge for vaccine design, requiring the identification of functionally important, conserved portions of the virus to target immunologically.…”
Section: Hcv Immune Evasion and Sequence Variabilitymentioning
confidence: 99%
“…Notably, within infected individuals, the virus actively evades the immune system [19] and evolves into a large number of quasispecies through error-prone replication [20]. This presents a major challenge for vaccine design, requiring the identification of functionally important, conserved portions of the virus to target immunologically.…”
Section: Hcv Immune Evasion and Sequence Variabilitymentioning
confidence: 99%
“…In patients, HCV circulates as a pool of quasispecies, viral variants which are genetically distinct and continually evolving due to a high viral mutation rate. [59] HCV variants reinfecting the liver graft are characterized by both enhanced entry in hepatocytes and escape from nAbs. [60] HCV has developed numerous strategies to avoid recognition by host humoral responses.…”
Section: Viral Evasion From Neutralizing Antibodiesmentioning
confidence: 99%
“…HCV is a small-enveloped, single-stranded RNA virus [4]. The envelope glycoproteins E1 and E2 are structural proteins located on the surface of HCV and responsible for binding to cells and entry.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was previously shown that these receptors individually are not sufficient to allow viral entry into hepatocytes [17,18]. Neutralizing epitopes have also been described that are different from the CD81 binding region [4]. The recently reported crystal structure of E2 has confirmed that a broadly conserved neutralizing epitopic stretch exists around the discontinuous CD81 binding site encompassing residues 412-424, 436-442 and 520-535 that harbour contact residues for many neutralizing antibodies [18].…”
Section: Introductionmentioning
confidence: 99%